The Miralles projection thinking and representation in the architecture of Enric Miralles - Fernández Contreras, Javier 1982- (Applied Research and Design Publishing, 2020)
This book explains both the origin and evolution of Miralles' system of representation, from his time as a student at the Barcelona School of Architecture to the latest projects he designed with Benedetta Tagliabue, including the heroic period with Carme Pinos. With previously unpublished drawings from the architect, it demonstrates on a fundamental level how the evolution of representation runs parallel to that of architecture, thus illustrating its indissolubility and mutual interdependence.0It is impossible to dissociate the evolution of the architecture of Enric Miralles from the development of his own system of representation. Beginning from a position inherited from his training at the Barcelona School of Architecture and his practice at the office of Viaplana-Pinon, where he acquired a liking for precision in drafting and a graphic style based exclusively on lines of the same thickness, Miralles soon developed a method defined by a customised use of orthographic projections, connected to a fragmented conception of the architectural plan and space itself
Keywords: Miralles, Enric -- 1955-2000